2016
DOI: 10.1037/emo0000206
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements are captured by a perceptually simple conditioned stimulus in the absence of explicit contingency knowledge.

Abstract: Past reports suggest that threatening materials can impact the efficiency of goal-directed behavior. However, questions remain about whether a conditional stimulus (CS) can capture attention as previous results may have been influenced by voluntary prioritization of a to-be-ignored CS. In 2 experiments, eye tracking was used to evaluate whether neutral, perceptually simple materials capture attention when they take on aversive properties via probabilistic fear conditioning with strict methods in place to elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 83 publications
(137 reference statements)
3
16
0
Order By: Relevance
“…In these studies, the threatening distractor captured not only covert attention but also the eyes more often than a nonthreatening distractor (Hopkins et al, 2016;Mulckhuyse & Dalmaijer, 2016). This was demonstrated even when participants were not explicitly aware of the contingency between the distractor and the threat (Hopkins et al, 2016). Other studies corroborate the findings that fear-conditioned distractors increase exogenously driven error saccades.…”
Section: Oculomotor Capture In Forced Choice and Spatial Cueingsupporting
confidence: 57%
See 4 more Smart Citations
“…In these studies, the threatening distractor captured not only covert attention but also the eyes more often than a nonthreatening distractor (Hopkins et al, 2016;Mulckhuyse & Dalmaijer, 2016). This was demonstrated even when participants were not explicitly aware of the contingency between the distractor and the threat (Hopkins et al, 2016). Other studies corroborate the findings that fear-conditioned distractors increase exogenously driven error saccades.…”
Section: Oculomotor Capture In Forced Choice and Spatial Cueingsupporting
confidence: 57%
“…1b). With this paradigm, it was found that endogenously driven saccades to the target are slowed more by a threatening distractor than by a nonthreatening distractor (Hopkins, Helmstetter, & Hannula, 2016;Mulckhuyse & Dalmaijer, 2016). These results indicate that the threatening distractor captured covert attention automatically and thereby delayed the programming of a saccade to a different location.…”
Section: Saccade Latency In Visual Searchmentioning
confidence: 85%
See 3 more Smart Citations